TURN-TAKING MARKER ETHNICAL BUGIS AND BETAWI AT INDONESIAN CONVERSION IN INDONESIA - Juanda, Juanda -; Aziz, Aziz (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Abstract.The conversation uses marker’s in the turn-taking. Turn-taking for participants has characteristics based on cultural backgrounds for the ethnically involved as participants. The purpose of this research is to analyze the interaction in the conversation and turn -taking and its marker’s. This research is a descriptive research. This research was used the approach of conversation analysis. The sources of data were drawn from the oral dialogue of ethnic Betawi and Bugis ethnic groups. The data retrieval by recording technique. The data analysis using Flow Model (Miles and A. Michael Huberman). The results this research show the interaction of turn taking conversations in Bugis and Betawi ethnic groups was dominated by more senior speakers and who have extensive knowledge insight. More junior speakers have a minimum speech turn. Pause or silence is a long time going when the topic will change. Transition markers in turn-taking are generally greetings and calls like Hen, Hah, Iye, Kok, Yah, Hm., Aah, Kalogitu, Ok, Goodnoon Madam! Good Afternoon Mas !, Yes, That, Lho, Nih. These markers are influenced by native language and ethnic backgrounds of the participants. Keywords: Markers, turn-taking, Bugis, and Betawi